Pelvic floor dysfunction in Mexican women - Loya Maldonado, Karen M.; Guerrero Reyes, Guadalupe; Gutierrez Gonzalez, Adrian; Reyes Alcaraz, Jennifer E.; Hernandez Velazquez, Ricardo; Robledo Torres, Alejandra; Treviño Cavazos, Omar; Leyva Vazquez, José I.; Chavez Loya, Danahe A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Pelvic floor dysfunction (PFD) is a term used to describe a variety of disorders that involve moderate to severe impairment of the pelvic floor muscles. Throughout their lives, up to 46% of women will present at least one form of PFD and may even have a combination of this pathology. These afflictions have a profound influence on women’s general well-being and quality of life, as well as being an immense economic burden for global health systems. Methods: This was a populational study which used surveys made in Google Forms of different questionnaires validated in Spanish [Urinary Incontinence Questionnaire (ICIQ), Female Sexual Function Index (IFSF), CPPQ Questionnaire for chronic pelvic pain, Wexner anal incontinence scale and quality of life] which were taken by women with access to social networks and who agreed to carry out an anonymous survey. Results: Seven hundred and twenty-one participants were evaluated, a total of 61.4% (443) responded positively to involuntary loss of urine, 35% had presented discomfort during sexual activity or lack of sexual interest, 14% had genital pain and 16% reported involuntary loss of feces or gas. Of all the patients that answered any of these questioners positively, only 33% had sought medical attention in the past. Conclusions: We concluded that in our population PFD is underdiagnosed. Our populations prevalence of urinary incontinence and pelvic pain is within the internationally described margins; anal incontinence is above international reports, and our population presented a lower prevalence of sexual dysfunction. With this new information we must impulse awareness to guide various preventive behaviors.